Encounter rate of large mammals in Thanigebyle range of Bhadra wildlife sanctuary, Karnataka - F, Pramod A; Kumara, Vijaya; T, Raghavendra Gowda H (International Multidisciplinary Research Journal, 2012)
Estimation of large mammals by using line transact method in the Thanigebyle range of Bhadra Wildlife Sanctuary during May 2009 to April 2010 in Thanigebyle range for four species of large herbivorous mammals viz., Chital (Axis axis), Sambar (Cervus unicolor), Barking deer (Muntiacus muntjak) and Gaur (Bosgaurus). The sanctuary was divided into several zones based on location and habitat types. Four permanent walking transect of 1 km were cut in different habitats of water holes for direct count and walk once in each month and four permanent vehicle transects of 18 kms were made. A total of 22 kms per month transect was evaluated including both walking transect and permanent vehicle transect of 4 kms and 18 kms respectively. This evaluation indicates that maximum number of individuals was observed in the walking transect when compared to vehicle transect for all the four species. During our study 21 Sambar, 161 Chital, 8 Barking deer and 21 Gaur was encountered. Chital was observed more in the study area. It also reveals that during pre monsoon and post monsoon seasons the number of individuals was observed to be higher.